The past, present and future of vaccination - Plotkin, Stanley (Henry Stewart Talks, 2007)
History of vaccines, with four lessons of vaccinology, New vaccines, including those against rotavirus, influenza, zoster and human papillomaviruses, New strategies of vaccine development, including recombinants, vectors, plasmid DNA and non|parenteral routes of administration
Archived at 2018/10/28